DINAMIKA TEGAKAN ALAM KULIM (Scorodocarpus borneensis Becc) DI AREAL BEKAS TEBANGAN IUPHHK-HA PT. SUKA JAYA MAKMUR KALIMANTAN BARAT - Ragina, Roberta; Manurung, Togar Fernando; Mariani, Yeni (JURNAL HUTAN LESTARI, 2013)
Kulim (Scorodocarpus borneensis Becc.) is a potential raw material used for a variety of needs, one of them is as building materials, Kulim is include of a group of first class of commercial wood, it is cause Kulim was harvested, so it is affect to the decreasing of Kulim natural. This research is aim to determine the dynamics of Kulim natural stands in logged over area of IUPHHK PT. Suka Jaya Makmur at annual work planning (RKT) 2007, 2009, 2011, and also the primary forest area. This research use a combination method between the transect and plot method. The result showed that the Important Value Index (IVI) of Kulim in logged over area of Poles level in RKT 2007, 2009 and 2011 respectively are 2,825; 12,534 and 6,508, while for the tree level the Important Value Index in RKT 2007, 2009, and 2011 respectively are 2,695; 6,936 and 7,812. In primary forest, the Important Value Index of Kulim in Poles level is 6,236 and for tree 3,903. Key words: Natural stand, Kulim (Scorodocarpus borneensis Becc.), Logged Area